Self-rated health and associated factors, Brazil, 2006 - Barros, Marilisa Berti de Azevedo; Zanchetta, Luane Margarete; Moura, Erly Catarina de; Malta, Deborah Carvalho (Revista de Saúde Pública, 2009)
OBJECTIVE: To assess prevalence of poor self-rated health and associated factors. METHODS: Data from 54,213 individuals aged >;18 years, collected by the Vigilância de Fatores de Risco e Proteção para Doenças Crônicas por Inquérito Telefônico (VIGITEL - Telephone-based Surveillance of Risk and Protective Factors for Chronic Diseases), in Brazilian state capitals and Federal District, in 2006, were analyzed. One resident of each household, with at least one fixed telephone line, was randomly selected from probability samples, subsequently answering the questionnaire. Independent variables analyzed were of a demographic, behavioral and self-reported morbidity nature. Prevalences and crude and adjusted prevalence ratios of poor self-rated health were estimated using Poisson regression. RESULTS: Poor self-rated health was more frequent in women, older individuals and those with lower level of education, without an occupation and living in state capitals of the Northern and Northeastern regions; among men prevalence of poor self-rated health was higher in the Southeastern region than in the Southern region. Smoking >; 20 cigarettes/day, lack of regular physical activity in leisure time and low weight or obesity were associated with poor self-rated health in both sexes; pre-obesity and frequent consumption of fruits and vegetables were significant in women, while not watching television was significant in men. Prevalence of poor self-rated health increased with the growth in the number of self-reported morbidities. Having four or five morbidities resulted in PR=11.4 in men and PR=6.9 in women, compared to those who did not have morbidities. CONCLUSIONS: Regional, sex and level of education inequalities were observed in the prevalence of poor self-rated health. In addition, its association with unhealthy behavior and comorbidities emphasize the need for strategies to promote healthy habits and those to control chronic diseases.